2011
DOI: 10.3892/mmr.2011.560
|View full text |Cite
|
Sign up to set email alerts
|

Induction of peroxisomal lipid metabolism in mice fed a high-fat diet

Abstract: Abstract. Peroxisomes catalyze a range of essential metabolic functions, mainly related to lipid metabolism. However, their roles in obesity have yet to be clarified. The aim of this study was to investigate the correlation between obesity and peroxisomal lipid metabolism, particularly very long-chain fatty acid (VLCFA) metabolism, gene expression of peroxisomal β-oxidation enzymes, peroxisomal ATP-binding cassette (ABC) transporter adrenoleukodystrophy (ABCD1) gene and its related gene, ABCD2, the elongation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
3
12
1
Order By: Relevance
“…A high-fat diet may induce obesity in mice (Kozawa et al 2011), rats (Mullen et al 2009), and humans (Boden 2011). Consistent with previous reports, the high-fat diet induced visceral adipose gain and obesity in both NL-HF and SL-HF rats.…”
Section: Discussionsupporting
confidence: 91%
“…A high-fat diet may induce obesity in mice (Kozawa et al 2011), rats (Mullen et al 2009), and humans (Boden 2011). Consistent with previous reports, the high-fat diet induced visceral adipose gain and obesity in both NL-HF and SL-HF rats.…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with previously published research, proteins associated with peroxisomes were considerably up-regulated in the mice that were fed a high-fat diet (Online Resource 3) [13]. Further, expression of mitochondrial proteins was broadly down-regulated [14].…”
Section: Resultssupporting
confidence: 88%
“…It was shown that HFD activates hepatic peroxisomal metabolism of very long-chain and branched-chain fatty acid (Kozawa et al 2011). In Zucker rats model of obesity, peroxisomal oxidation products were shown to enter mitochondria, providing the possibility to maintain lipid disposal, even under insulin resistance condition (Noland et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During fasting, it decreased the expression of genes involved in the amino acids metabolism (Kersten et al 2001). It was upregulated in mice fed with HFD (Kozawa et al 2011). Beside metabolic processes, PPARα is also involved in regulation of inflammation processes.…”
Section: Discussionmentioning
confidence: 99%